KNOWLEDGE, ATTITUDE AND PRACTICE FOR BREAST CANCER RISK FACTORS AND SCREENING MODALITIES IN STAFF NURSES OF AYUB TEACHING HOSPITAL ABBOTTABAD - Ahmad, Sheraz; Qureshi, Ahmad Nadim; Atta, Sania; Gul, Mahwish; Rizwan, Muhammad; Ahmad, Sohail; Riaz, Ayesha; Gul, Muniba; Zaman, Shafaq; Johnny, Nita (Journal of Ayub Medical College Abbottabad, 2011)
Background: Breast cancer is the commonest cancer modality in female worldwide. Avoiding the risk factors can reduce its incidence and adhering to screening and early detection can reduce its mortality. A sufficient knowledge regarding the risk factors and screening modalities is therefore essential. We assessed the knowledge level about these parameters in our staff nurses. Methods: A self-administered questionnaire survey was performed. Knowledge regarding the risk factors and screening modalities were categorised into good, fair, poor and very poor categories. Results: Knowledge regarding most of the factors was found to be fair. A few things were termed as good knowledge like role of breast-feeding in protecting against breast cancer. Practice regarding the screening modalities was not satisfactory. Only a few nurses had good knowledge of the risk factors and screening modalities. Practice of the Screening modalities was also poor. Conclusion: There is a need to improve the nursing curriculum, training at the workplace and motivate them for screening practices. They should be encouraged to talk to their patients and their female attendants about prevention and early detection of breast cancer. Keywords: Breast cancer, BSE, knowledge